Analisa thermogravimetry pada pirolisis limbah pertanian - Yulius Widiardi Pratomo Wiyoto; Eko Prasetyo Budiana; Dwi Aries Himawanto (Badan Kerja Sama Teknik Mesin Indonesia, 2016)
The potential for biomass to supply much larger amounts of useful energy with reduced environmental impacts. Pyrolysis and other thermochemical conversion processes offer an important opportunity for utilization of biomass and waste. Pyrolysis of biomass can be described as the direct thermal decomposition of the material in the absence of oxygen to obtain an array of solid (char), liquid (tar) and gas products. Pyrolysis agricultural waste are produced tar, char and organic component. The thermal behaviour of selected biomass as rice straw, cassava peel, rice husk, saw dust and corncob was investigated using a thermogravimetric analyzer (TGA). Thermogravimetry has proved to be a useful tool in elucidating the decomposition of various biomass material. In thermogravimetric analyzer have RS Key and Adam Utility to convert data from TGA to computer. Sampel weight used 20 gram with heating rate 15 oC/min, maximal temperature 600 oC, holding time 10 minute and irrigated with 100 ml/min gas nitrogen. Result in this research indicates that drying process occur loss weight agricultural residu consecutive 5,35 %, 9,28 %, 12,91 %, 7,83 % and 7,82% and volatile matter in rice straw: 53,16 %, cassava peel: 60,28 %, rice husk: 48,24 %, saw dust: 64,32 % and corncob: 66,71 %.